Anti-diabetic activity of a sulfated galactoarabinan with unique structural characteristics from Cladophora oligoclada (Chlorophyta). (15th February 2022) - He, Meijia; Hao, Jiejie; Feng, Changning; Yang, Yajing; Shao, Zhuling; Wang, Lei; Mao, Wenjun
Abstract: The polysaccharide from green alga Cladophora oligoclada, OHSS2, was a sulfated galactoarabinan which was constituted by a backbone of (1 → 4)-β-l -arabinopyranose units with partial sulfate at C-3 of (1 → 4)-β-l -arabinopyranose units. The side chains containing (1 → 4)-β-l -arabinopyranose, (1 → 4)-β-d -galactopyranose and/or (1 → 4, 6)-β-d -galactopyranose units were in C-2/C-3 of (1 → 4)-β-l -arabinopyranose units. OHSS2 had strong anti-diabetic activity in vitro assessed by inhibition of human islet amyloid polypeptide (hIAPP) aggregation. The mechanism analysis of anti-diabetic activity showed that OHSS2 diminished the production of intracellular reactive oxygen species and alleviated hIAPP aggregation-induced oxidative stress in NIT-1 cells. OHSS2 stabilized mitochondrial membrane potential, and enhanced the mitochondrial complex I, II or III activity and ATP level. Thus, OHSS2 effectively protected mitochondria from hIAPP aggregation-induced damage. Furthermore, OHSS2 was co-localized with mitochondria and could have a direct influence on mitochondrial function. These results revealed that OHSS2 had potential as a novel anti-diabetic agent. Highlights: Polysaccharide from Cladophora oligoclada (Chlorophyta), OHSS2, is a sulfated galactoarabinan. OHSS2 is constituted by a backbone of (1 → 4)-β-L-arabinopyranosyl units partially sulfated at C-3. OHSS2 significantly inhibits hIAPP aggregation and has strong anti-diabetic activity in vitro . OHSS2 effectively protects mitochondria from hIAPP aggregation-induced damage. OHSS2 is co-localized with mitochondria and can have direct influence on mitochondrial function.